Islam And Christian: Religious Harmony - Regina, Dinda Alfa; Wijayanti, Yolanda Nur (Institut Agama Islam Negeri Kerinci, 2022)
This research aims to understand and know the factors and patterns of daily life adopted by the people of Patok Empat village so that they can live in harmony with each other even in the circumstances with different beliefs. Furthermore, this research wants to understand and find out how the people of Patok Empat Village view the concept of inter-religious harmony. The method used in this research is descriptive qualitative. Data collection techniques used are observation, interviews, and documentation. The results of this study are the creation of harmony in Patok Empat Village because every community with different religious backgrounds is open to each other and accepts the existence of other religions. The existence of religious diversity in Patok Empat Village does not necessarily make their interaction or social relations rigid. Instead, it makes them respect each other, regardless of the existence of majority and minority religions. They always instilled a sense of brotherhood and cooperation. In addition, some factors affect harmony: family ties, mutual respect, and respect between religious communities.